Hubungan Mutu Pelayanan Kesehatan Terhadap Tingkat Kepuasan Pasien di Poliklinik TB Paru Puskesmas Bihbul Kecamatan Margahayu Bandung - Mujiharti, Rahayu; Mudmainah, Mudmainah; Sepriani, Eka Galih (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
The quality of health services on patient satisfaction is a reflection of the quality of service received. The higher the quality of health services provided, the higher the patient satisfaction. This study aims to analyze and determine the relationship between the quality of health services and patient satisfaction at the Pulmonary TB Polyclinic, Bihbul Health Center, Margahayu District, Bandung. This research is quantitative research using a cross-sectional research design approach. The research was carried out at the Bihbul Community Health Center, Margahayu District, Bandung in May – July 2023 with 10 participants. The research instrument used was a questionnaire. Data were analyzed using the Pearson Product Moment Test to determine the relationship between health service quality and patient satisfaction. It is known that the results of statistical analysis show a significance value of 0.000 (p = 0.000), which indicates that service quality has a significant effect on patient satisfaction. So Bihbul Health Center can improve the quality of health services because efficient and effective service quality can increase patient satisfaction, especially at the Pulmonary TB Polyclinic.